Changes to GFAP Immunoreactive Astrocytes in medial prefrontal cortex following exposure to chronic stress and antioxidant supplementation in rat model - Asari, Mohd Asnizam; Md Nawi, Faizah; Mohd Amin, Mohammad Syabil Ikhwan; Mohd Yusof, Nurul Aiman; Kuttulebbai Naina Mohamed Salam, Sirajudeen (Universiti Putra Malaysia (UPM), 2023)
Introduction: Astrocytes are responsible for many essential functions of neurons in CNS. It has been recognised that chronic stress affects the morphology of astrocyte. Natural antioxidant such as honey has been used as one of the therapeutic strategies to lessen the damaging effect of chronic stress on our body. Therefore, the aim of the study is to explore the effect of natural antioxidant, Tualang honey (TH) on the morphology of astrocytes following chronic stress exposure. Methods: Thirty-two male rats were randomly divided into the 4 groups: (i) control, (ii) stress, (iii) honey, (iv) stress plus honey groups.TH was administered via oral gavage at dose of 1.0 g/kg body weight pre and post experiment. Chronic stress was exposed to animals in group (ii) and (iv) for consecutive 21 days. Anti GFAP immunohistochemistry method was employed to label astrocytes in the medial prefrontal cortex. The number of GFAP+ astrocytes and several parameters related to astrocyte processes were measured. Results: The present study showed that chronic stress reduced the GFAP immunoreactive astrocyte number and percentage of GFAP immunoreactive material. Chronic stress also caused a reduction in astrocyte process ramification as indicated by a reduction in astrocyte total number of processes, average length of processes and maximum number of intersections. However, antioxidant treatment using TH could not reverse these stress-induced changes to the astrocytes. Conclusion: These results demonstrate that chronic stress decreases the number of GFAP immunoreactive astrocyte and cause shrinking of astrocyte processes in stress-sensitive brain region, but these changes cannot be reversed by antioxidant treatment.